The Effect of Financial Literacy, Motivation, and Herding Effect on Investment Decisions with Emotional Intelligence as a Moderating Variable - Vira Regina Salsabila; Tri Neliana (Indonesian Journal of Business Analytics, 2025)
With emotional intelligence serving as the moderating variable, this study investigates how financial literacy, investment motivation, and herding effect influence investment decisions. The quantitive research targets active students (1997-2012) in Ciayumajakuning who invest in capital market, using purposive sampling (135 sampels). The analysis technique used is Moderate Regression Analysis (MRA). The results in this study indicate that financial literacy and herding effect have a positive value and have a significant effect on investment decisions, while investment motivation has no significant effect, and each independent variable’s impact on the dependent variable cannot be moderated by emotional intelligence variables.